Back Cover: NMR Crystallography of an Oxovanadium(V) Complex by an Approach Combining Multinuclear Magic Angle Spinning NMR, DFT, and Spin Dynamics Simulations (ChemPhysChem 8/2015). Issue 8 (8th June 2015) - Pourpoint, Frédérique; Yehl, Jenna; Li, Mingyue; Gupta, Rupal; Trébosc, Julien; Lafon, Olivier; Amoureux, Jean‐Paul; Polenova, Tatyana
Abstract : Onp. 1619 F. Pourpoint, T. Polenova et al. describe an approach that combines multinuclear 13 C/ 51 V solid‐state NMR spectroscopy, density functional theory, and spin dynamics numerical simulations, thus allowing new insights into the structure of bioinorganic vanadium solids to be obtained.